Insulation coated soft magnetic powder, pressed powder core, magnetic components, electronic equipment
By covering the insulator on the soft magnetic powder and processing it at high temperature, the problem of increasing eddy current loss under high frequency is solved, and the magnetic characteristics and high temperature resistance of the magnetic components are improved.
Patent Information
- Application Number
- CN202210271346.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-04-27
- Filing Date
- 2019-04-25
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2039-04-25
AI Technical Summary
Driven by high-frequency switching power supply, the Joule loss (eddy current loss) caused by eddy current in the magnetic component is significantly increased, and soft magnetic powders are prone to coagulation during ultra-high temperature heat treatment, resulting in a decrease in formability and magnetic properties.
The soft magnetic powder is coated with an insulator, which contains core particles and insulating particles. The core particles have a base and an oxide film. The insulating particles are provided on the surface of the core particles, and the average particle size is kept at 90% or more than 110% by heat treatment at 1000°C to ensure the insulation and high temperature resistance between the particles.
It effectively reduces eddy current loss, improves the magnetic characteristics and forming density of the powdered magnetic core, and ensures reliability and performance stability at high temperatures.
Smart Images

Figure CN114613566B_ABST
Abstract
Description
[0001] This application is a divisional application of a patent application with an application date of April 25, 2019, application number 201910342893.0, and invention name "Insulation-coated soft magnetic powder, pressed powder core, magnetic element, electronic device", and all its contents are incorporated herein by reference. Technical Field
[0002] The invention relates to insulator-coated soft magnetic powder, pressed powder magnetic core, magnetic element, electronic equipment and moving body. Background Art
[0003] In recent years, portable devices such as notebook computers have become increasingly smaller and lighter, but in order to achieve both miniaturization and high performance, switching power supplies need to be made higher in frequency. Currently, the driving frequency of switching power supplies is increasing to hundreds of kHz or more, and as a result, magnetic components such as choke coils and inductors built into portable devices also need to respond to higher frequencies.
[0004] However, when the driving frequency of these magnetic elements is increased, the Joule loss (eddy current loss) caused by eddy current in the magnetic core of each magnetic element increases significantly. Therefore, the eddy current loss is reduced by insulating the particles of the soft magnetic powder contained in the magnetic core from each other.
[0005] For example, Patent Document 1 discloses a soft magnetic metal particle powder in which an insulating layer provided on the particle surface is formed of fine oxide particles of aluminum or the like. It is also disclosed that such a soft magnetic metal particle powder is produced by applying mechanical energy formed by compression or shearing force to the fine oxide particles.
[0006] Patent Document 1: Japanese Patent Application Publication No. 2009-188270
[0007] In recent years, it has been sought to more reliably remove the strain remaining in the soft magnetic powder by performing a heat treatment at an ultra-high temperature (for example, at or above the sintering temperature), thereby reducing the coercive force and achieving a reduction in hysteresis loss.
[0008] However, even the soft magnetic metal particle powder described in Patent Document 1 may sometimes aggregate between metal particles during heat treatment at ultra-high temperatures exceeding the sintering temperature. If such aggregation occurs, the properties of the powder are impaired, and thus the formability of the soft magnetic metal particle powder is reduced. Therefore, sufficient filling properties cannot be obtained during powder compacting, and the magnetic properties of the powder core are reduced. Summary of the invention
[0009] The present invention has been made to solve the above-mentioned technical problems, and can be implemented as the following application examples.
[0010] The insulating material coated soft magnetic powder involved in the application example of the present invention is characterized in that it has core particles and insulating particles, the core particles have a base and an oxide film, the base contains a soft magnetic material, the oxide film is arranged on the surface of the base and contains oxides of elements contained in the soft magnetic material, the insulating particles are arranged on the surface of the core particles and have insulating properties, and the average particle size of the insulating material coated soft magnetic powder after heat treatment at 1000°C is more than 90% and less than 110% of the average particle size before the heat treatment.
[0011] A powder magnetic core according to an application example of the present invention is characterized by including the above-mentioned insulator-coated soft magnetic powder.
[0012] A magnetic element according to an application example of the present invention is characterized by including the above-described powder magnetic core.
[0013] An electronic device according to an application example of the present invention is characterized by including the above-mentioned magnetic element.
[0014] A moving body according to an application example of the present invention is characterized by including the above-mentioned magnetic element. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a cross-sectional view showing one particle of the insulator-coated soft magnetic powder according to an embodiment of the present invention.
[0016] Figure 2 Yes means Figure 1 The cross-sectional view of a strain example of soft magnetic particles coated with an insulator is shown.
[0017] Figure 3 It is a longitudinal sectional view showing the structure of the powder coating device.
[0018] Figure 4 It is a longitudinal sectional view showing the structure of the powder coating device.
[0019] Figure 5 It is a schematic diagram (plan view) showing a choke coil to which the magnetic element according to the first embodiment is applied.
[0020] Figure 6 It is a schematic diagram (perspective perspective view) showing a choke coil to which the magnetic element according to the second embodiment is applied.
[0021] Figure 7 It is a perspective view showing the structure of a mobile (or notebook) personal computer to which an electronic device including a magnetic element according to an embodiment is applied.
[0022] Figure 8It is a plan view showing the structure of a smartphone to which an electronic device including the magnetic element according to the embodiment is applied.
[0023] Fig. 9 It is a perspective view showing the structure of a digital camera to which an electronic device including the magnetic element according to the embodiment is applied.
[0024] Fig.10 It is a perspective view showing a vehicle to which a moving body including a magnetic element according to the embodiment is applied.
[0025] Description of Reference Numerals
[0026] 1. Insulator-coated soft magnetic particles; 1', insulator-coated soft magnetic particles; 2, core particles; 2a, base; 2b, oxide film; 3, insulating particles; 10, choke coil; 11, pressed powder core; 12, conductor; 20, choke coil; 21, pressed powder core; 22, conductor; 100, display unit; 101, powder coating device; 110, container; 120, arm; 130, rotating shaft; 140, chisel; 150, scraper; 1000, magnetic element; 1100, personal computer computer; 1102, keyboard; 1104, main body; 1106, display unit; 1200, smart phone; 1202, operation button; 1204, receiver; 1206, microphone; 1300, digital camera; 1302, housing; 1304, light receiving unit; 1306, shutter button; 1308, memory; 1312, video signal output terminal; 1314, input / output terminal; 1430, television monitor; 1440, personal computer; 1500, automobile. DETAILED DESCRIPTION
[0027] Hereinafter, the insulator-coated soft magnetic powder, the powder magnetic core, the magnetic element, the electronic device, and the moving body of the present invention will be described in detail based on the preferred embodiments shown in the drawings.
[0028] [Insulation coated soft magnetic powder]
[0029] First, the insulator-coated soft magnetic powder according to the present embodiment will be described.
[0030] Figure 1 This is a cross-sectional view showing one particle of the insulator-coated soft magnetic powder according to an embodiment of the present invention. Note that in the following description, one particle of the insulator-coated soft magnetic powder is also referred to as an "insulator-coated soft magnetic particle".
[0031] Figure 1The insulator-coated soft magnetic particle 1 shown comprises: a core particle 2 having a base 2a containing a soft magnetic material and an oxide film 2b provided on the surface of the base 2a; and an insulating particle 3 provided on the surface of the core particle 2 and having insulating properties. In addition, the oxide film 2b comprises an oxide of an element contained in the soft magnetic material. In addition, the insulator-coated soft magnetic particle 1 satisfies the relationship that the average particle size after heat treatment at 1000°C is not less than 90% and not more than 110% of the average particle size before heat treatment before the heat treatment.
[0032] In such an insulator-coated soft magnetic particle 1, first, the insulation between particles is ensured by providing the insulating particles 3 on the surface of the core particle 2. Therefore, by forming such an insulator-coated soft magnetic particle 1 into a predetermined shape, a powder core that can realize a magnetic element with low eddy current loss can be manufactured.
[0033] In particular, the presence of insulating particles 3 on the surface of the insulating material-coated soft magnetic particles 1 can more reliably suppress contact between the core particles 2. This ensures insulation resistance between the core particles 2 and reduces eddy current loss.
[0034] In addition, such an insulator-coated soft magnetic particle 1 is configured so that the ratio of the average particle size after heat treatment at 1000°C to the average particle size before heat treatment before the heat treatment is within the aforementioned range. That is, the insulator-coated soft magnetic particle 1 places the insulating particles 3 between the core particles 2, so that even after heat treatment at high temperature, it is not easy to produce coagulation, adhesion, etc. between particles. Therefore, even after heat treatment, it has the same average particle size as before heat treatment, and good filling properties during powder compacting can be obtained. As a result, the insulator-coated soft magnetic particle 1 exhibits good handling properties as a powder even after heat treatment at high temperature, and a powder compact with good magnetic properties can be manufactured.
[0035] Furthermore, according to such insulator-coated soft magnetic particles 1, since they have high resistance to high temperatures, it is possible to realize, for example, a powder magnetic core and a magnetic element with high reliability at high temperatures. Therefore, such a powder magnetic core and a magnetic element can maintain excellent reliability even when used in an environment where high temperatures are maintained for a long time, such as in an engine room.
[0036] in addition, Figure 2 Yes means Figure 1 The cross-sectional view of a strain example of soft magnetic particles coated with an insulator is shown.
[0037] Compared to the above Figure 1 In the insulating material-coated soft magnetic particle 1 shown in FIG. 1 , the insulating particle 3 is in contact with the surface of the core particle 2. Figure 2In the insulator-coated soft magnetic particle 1 ′ shown, a part of the insulating particles 3 is buried in the surface of the core particle 2 , specifically, in an oxide film 2 b described later.
[0038] In such an insulating material-coated soft magnetic particle 1', a larger contact area between the core particle 2 and the insulating particle 3 can be ensured. Therefore, the probability of the insulating particle 3 falling off from the core particle 2 can be particularly reduced. As a result, an insulating material-coated soft magnetic particle 1' can be obtained in which agglomeration and adhesion between particles are particularly unlikely to occur even after a heat treatment at a high temperature.
[0039] It should be noted that if Figure 2 As shown, a part of the plurality of insulating particles 3 may be buried in the oxide film 2 b , or all of the insulating particles 3 may be buried in the oxide film 2 b .
[0040] In addition, in one insulating particle 3, a part of it may be buried in the oxide film 2b, or the whole of it may be buried in the oxide film 2b.
[0041] The following describes the manufacturing process in detail. Figure 1 An example of a method of coating the soft magnetic particles 1 with an insulating material is shown.
[0042] One example of such a production method is a method of mechanically adhering insulating particles 3 having insulating properties to core particles 2. Thus, the insulating particles 3 are adhered to the surface of the core particles 2, and the above-mentioned insulator-coated soft magnetic particles 1 can be obtained.
[0043] Figure 3 as well as Figure 4 Each of the diagrams is a longitudinal sectional view showing the structure of a powder coating device.
[0044] [1] First, prepare the core particles 2 and the insulating particles 3 (see Figure 3 ).
[0045] The core particles 2 are particles containing a soft magnetic material.
[0046] The core particle 2 according to the present embodiment includes a base 2 a including a soft magnetic material, and an oxide film 2 b provided on the surface of the base 2 a and including an oxide of an element included in the soft magnetic material.
[0047] In such a core particle 2, since the oxide film 2b having lower conductivity than the base 2a is provided, the insulation resistance between the core particles 2 is improved even in the core particles 2 themselves. Thus, in the powder compact formed by compressing the insulator-coated soft magnetic particles 1, the eddy current loss is further reduced.
[0048] As the soft magnetic material contained in the base 2a, for example, in addition to various Fe alloys such as pure iron, silicon steel (Fe-Si alloy), permalloy (Fe-Ni alloy), permalloy (Fe-Co alloy), Fe-Si-Al alloy such as sendust, Fe-Cr-Si alloy, Fe-Cr-Al alloy, etc., various Ni alloys, various Co alloys, etc. are listed. Among them, various Fe alloys are preferably used from the perspective of magnetic properties such as magnetic permeability and magnetic flux density, and productivity such as cost.
[0049] The crystallinity of the soft magnetic material is not particularly limited, and the soft magnetic material may be crystalline, amorphous (amorphous material), or microcrystalline (nanocrystalline).
[0050] It should be noted that, in the base portion 2a, the soft magnetic material is preferably used as the main material, but impurities may also be contained.
[0051] On the other hand, the oxide contained in the oxide film 2b is an oxide of an element contained in the soft magnetic material contained in the base 2a. Therefore, in the case where the soft magnetic material contained in the base 2a is, for example, a Fe-Cr-Si alloy, the oxide film 2b only needs to contain at least one of iron oxide, chromium oxide, and silicon oxide. In addition, the Fe-Cr-Si alloy sometimes also contains elements (other elements) other than the main elements such as Fe, Cr, and Si. In this case, the oxide of the other element may be replaced by the oxide of the main element, or both the oxide of the main element and the oxide of the other element may be contained.
[0052] Examples of oxides included in the oxide film 2b include iron oxide, chromium oxide, nickel oxide, cobalt oxide, manganese oxide, silicon oxide, boron oxide, phosphorus oxide, aluminum oxide, magnesium oxide, calcium oxide, zinc oxide, titanium oxide, vanadium oxide, and cerium oxide, and the oxide may contain one or more of them.
[0053] Among them, the oxide film 2b preferably contains a glass-forming component or a glass-stabilizing component. Thus, for example, when the insulating particles 3 contain oxides, the oxide film 2b plays a role in promoting the insulating particles 3 to adhere to the oxide film 2b. That is, the glass-forming component or the glass-stabilizing component produces an interaction such as vitrification with the oxide contained in the insulating particles 3, promoting the insulating particles 3 to adhere to the oxide film 2b more firmly. As a result, the insulating particles 3 are not easy to fall off from the surface of the core particles 2, and the insulating material-coated soft magnetic particles 1 with high reliability and low insulation properties can be obtained.
[0054] In addition, by vitrification, even in an environment such as repeated high and low temperatures, it is difficult to generate gaps between the core particles 2 and the insulating particles 3. Therefore, it is possible to suppress the reduction in insulation due to, for example, moisture entering the gaps. Therefore, in this aspect, an insulating material-coated soft magnetic particle 1 with good high temperature resistance can also be obtained.
[0055] In other words, the insulating particles 3 are preferably composited with the oxide film 2 b . This allows the core particles 2 and the insulating particles 3 to adhere more firmly to each other, and reduces the decrease in insulation even at high temperatures.
[0056] It should be noted that the composite formation refers to a state in which the insulating particles 3 are sunken into the oxide film 2 b or a state in which components of the insulating particles 3 and the oxide film 2 b are mutually diffused.
[0057] Examples of the glass-forming component include silicon oxide, boron oxide, and phosphorus oxide.
[0058] On the other hand, examples of glass stabilizing components include aluminum oxide and the like.
[0059] Even among such oxides, the oxide film 2b preferably contains at least one of silicon oxide, aluminum oxide, and chromium oxide. Since silicon oxide is a glass-forming component and aluminum oxide is a glass-stabilizing component, it is easy to interact with the oxide contained in the insulating particles 3 to produce vitrification or the like. Therefore, the insulating particles 3 are more firmly adhered to the oxide film 2b, and the insulating material-coated soft magnetic particles 1 with high reliability and whose insulating properties are not easily reduced can be obtained. In addition, since chromium oxide is chemically stable, the insulating material-coated soft magnetic particles 1 with high reliability and whose insulating properties are not easily reduced even at high temperatures can be obtained.
[0060] It should be noted that the presence or absence of the oxide film 2b can be determined based on the concentration distribution of oxygen atoms in the direction from the surface toward the center of the core particle 2 (hereinafter referred to as the "depth direction"). That is, when the concentration distribution of oxygen atoms in the depth direction of the core particle 2 is obtained, the presence or absence of the oxide film 2b can be evaluated based on the distribution.
[0061] Such a concentration distribution can be obtained, for example, by depth analysis of Auger electron spectroscopy using sputtering. In this analysis, ions are collided with the surface of the nuclear particle 2, and the atomic layer is gradually peeled off while the electron beam is irradiated to the nuclear particle 2, and the identification and quantification of atoms are performed based on the kinetic energy of the Auger electrons released from the nuclear particle 2. Therefore, by converting the time required for sputtering into the thickness of the atomic layer peeled off by sputtering, the relationship between the depth from the surface of the nuclear particle 2 and the composition ratio can be obtained.
[0062] In addition, since a position at a depth of 300 nm from the surface of the core particle 2 can be regarded as sufficiently deep from the surface, the oxygen concentration at this position can be regarded as the oxygen concentration inside the core particle 2 .
[0063] In this way, the thickness of the oxide film 2b can be calculated by calculating the relative amount of the oxygen concentration in the depth direction from the surface of the core particle 2. Specifically, the core particle 2 is oxidized from the surface to the inside during its manufacturing process, but as long as the oxygen concentration obtained by the above analysis is within the range of ±50% of the oxygen concentration in the above internal part, it can be considered that the oxide film 2b does not exist in the part to be analyzed. On the other hand, as long as the oxygen concentration obtained by the above analysis is higher than +50% of the oxygen concentration in the above internal part, it can be considered that the oxide film 2b exists in the part to be analyzed.
[0064] Therefore, by repeatedly performing such evaluation, the thickness of the oxide film 2 b can be obtained.
[0065] Note that the type of oxide included in the oxide film 2 b can be identified by, for example, X-ray photoelectron spectroscopy or the like.
[0066] The thickness of the oxide film 2b measured in this way is preferably 5 nm to 200 nm, and more preferably 10 nm to 100 nm. Thus, the core particle 2 itself also has insulating properties. Therefore, under the joint action of the insulating particles 3, an insulating material-coated soft magnetic particle 1 with higher insulating properties can be obtained.
[0067] In addition, oxide film 2b of such thickness can further improve the adhesion strength between oxide film 2b and insulating particles 3. Thus, insulating particles 3 are less likely to fall off the surface of core particle 2, and the reliability of insulating material-coated soft magnetic particles 1 can be further improved.
[0068] It should be noted that if the thickness of the oxide film 2b is lower than the lower limit, the thickness of the oxide film 2b is thin, so there is a risk that the insulation between the particles of the insulator-coated soft magnetic particles 1 is reduced, or the insulating particles 3 are easily detached from the oxide film 2b. On the other hand, if the thickness of the oxide film 2b is higher than the upper limit, the thickness of the oxide film 2b is too thick, so the volume of the base 2a is relatively reduced, and there is a risk that the magnetic properties of the powder compact formed by pressing the insulator-coated soft magnetic particles 1 are reduced.
[0069] Such core particles 2 can also be manufactured by any method, for example, by various powdering methods such as atomization (such as water atomization, gas atomization, high-speed rotating water flow atomization, etc.), reduction, carbonyl method, and pulverization.
[0070] Among them, it is preferred to use core particles produced by water atomization or high-speed rotating water flow atomization as core particles 2. According to the water atomization method and the high-speed rotating water flow atomization method, extremely fine powders can be produced efficiently. In addition, since the contact between molten metal and water is used to pulverize in the water atomization method and the high-speed rotating water flow atomization method, an oxide film 2b with a suitable film thickness is formed on the surface of the core particle 2. As a result, the core particle 2 having an oxide film 2b with a suitable film thickness can be produced efficiently.
[0071] It should be noted that the thickness of the oxide film 2b can be adjusted by, for example, the cooling rate of the molten metal when manufacturing the core particle 2. Specifically, the oxide film 2b can be thickened by slowing down the cooling rate.
[0072] On the other hand, the insulating particles 3 are particles containing an insulating material.
[0073] As insulating materials, various ceramic materials are listed, specifically, aluminum oxide, magnesium oxide, titanium oxide, zirconium oxide, silicon oxide, iron oxide, potassium oxide, sodium oxide, calcium oxide, chromium oxide, boron nitride, silicon nitride, silicon carbide, etc., and a material containing one or more of them is used.
[0074] Among them, the insulating particles 3 preferably contain at least one of aluminum oxide, silicon oxide, zirconium oxide and silicon nitride. They have high hardness and softening point (melting point). Therefore, the insulator-coated soft magnetic particle 1 having such insulating particles 3 is easy to maintain the particle shape of the insulating particles 3 even when subjected to a compressive load. Therefore, it is possible to obtain an insulating material-coated soft magnetic particle 1 in which the insulation between particles is not easily reduced even when pressed into powder, and it is possible to perform powder pressing under high pressure and manufacture a powder compact with good magnetic properties. In addition, the insulating material-coated soft magnetic particle 1 having such insulating particles 3 has excellent heat resistance. Therefore, it is possible to realize an insulating material-coated soft magnetic particle 1 in which the average particle size changes little even after undergoing heat treatment at high temperature, and the powder characteristics such as filling property in a forming mold are not easily reduced.
[0075] In addition, it is preferred to use a material with a higher hardness as the insulating material. Specifically, a material with a Mohs hardness of 6 or more is preferred, and a material with a Mohs hardness of 6.5 or more and 9.5 or less is more preferred. According to such an insulating material, it is easy to maintain the particle shape of the insulating particles 3 even when subjected to a compressive load. Therefore, even when pressed, the insulation between particles is not easily reduced, and the insulating material-coated soft magnetic particles 1 can be obtained, which can be pressed under high pressure and can produce a pressed powder body with good magnetic properties.
[0076] Furthermore, the insulating material having such a Mohs hardness has a high melting point and is therefore excellent in heat resistance. Therefore, it is possible to realize the insulating material coated soft magnetic particles 1 whose average particle size changes little even after heat treatment at high temperature and whose powder properties such as filling property in a molding die are not easily reduced.
[0077] The average particle size of the insulating particles 3 is not particularly limited, but is preferably 1 nm to 500 nm, more preferably 5 nm to 300 nm, and further preferably 8 nm to 100 nm. By setting the average particle size of the insulating particles 3 within the above range, when the insulating particles 3 are mechanically adhered to the core particles 2 in the steps described later, a necessary and sufficient pressure can be applied to the insulating particles 3. As a result, the insulating particles 3 can be well adhered to the core particles 2.
[0078] Note that the average particle size of the insulating particles 3 is a particle size at which 50% of the particles are accumulated from the smaller diameter side in a mass-based cumulative distribution measured by a laser diffraction particle size distribution measuring device.
[0079] In addition, the average particle size of the insulating particles 3 is preferably about 0.01% to about 10.0% of the average particle size of the core particles 2, and more preferably about 0.05% to about 5.0%. If the average particle size of the insulating particles 3 is within the above range, the insulator-coated soft magnetic particles 1 have sufficient insulation, and when the collection of the insulator-coated soft magnetic particles 1 is pressurized and formed to produce a powdered magnetic core, the occupancy rate of the core particles 2 in the powdered magnetic core is prevented from being significantly reduced. As a result, an insulator-coated soft magnetic particle 1 capable of producing a powdered magnetic core with low eddy current loss and excellent magnetic properties such as magnetic permeability and magnetic flux density can be obtained.
[0080] It should be noted that the average particle size of the core particles 2 is preferably 1 μm to 50 μm, more preferably 2 μm to 30 μm, and further preferably 3 μm to 15 μm. If the average particle size of the core particles 2 is within the above range, an insulating material-coated soft magnetic particle 1 can be obtained for manufacturing a powder magnetic core having low eddy current loss and excellent magnetic properties such as magnetic permeability and magnetic flux density.
[0081] In addition, the amount of the insulating particles 3 added is preferably 0.1% by mass to 5% by mass of the core particles 2, and more preferably 0.3% by mass to 3% by mass. If the amount of the insulating particles 3 added is within the above range, the insulator-coated soft magnetic particles 1 have sufficient insulation, and when the collection of the insulator-coated soft magnetic particles 1 is pressurized and formed to produce a powdered magnetic core, the occupancy rate of the core particles 2 in the powdered magnetic core is prevented from being significantly reduced. As a result, an insulator-coated soft magnetic particle 1 capable of producing a powdered magnetic core with low eddy current loss and excellent magnetic properties such as magnetic permeability and magnetic flux density can be obtained.
[0082] [2] Next, the insulating particles 3 are mechanically bonded to the core particles 2. In this way, the insulating material-coated soft magnetic particles 1 can be obtained.
[0083] This mechanical adhesion is produced by pressing the insulating particles 3 against the surface of the core particles 2 with a high pressure. Figure 3 as well as Figure 4 The powder coating apparatus 101 shown in the figure produces the above-mentioned mechanical adhesion to produce the insulator-coated soft magnetic particles 1.
[0084] As devices for causing mechanical compression and friction to the core particles 2 and the insulating particles 3, there are listed various pulverizers such as hammer mills, disc mills, roller mills, ball mills, planetary mills, jet mills, Angmill (registered trademark), high-speed elliptical mixers, Mix Muller (registered trademark), Jacobson mills, Mechanofusion (registered trademark), Hybridization (registered trademark) and other friction mixers. Here, as an example, a container 110 and a chisel 140 rotating along the inner wall of the container are used. Figure 3 and Figure 4 The powder coating device 101 (friction mixer) shown will be described.
[0085] The powder coating device 101 includes a cylindrical container 110 and a rod-shaped arm 120 provided in the container 110 in a radial direction.
[0086] The container 110 is made of a metal material such as stainless steel, and applies mechanical compression and friction to the mixture of the core particles 2 and the insulating particles 3 put into the container.
[0087] In addition, a rotation shaft 130 is inserted through the center of the longitudinal direction of the arm 120, and the arm 120 is provided to be freely rotatable around the rotation shaft 130. It should be noted that the rotation shaft 130 is provided to coincide with the central axis of the container 110.
[0088] In addition, a chisel 140 is provided at one end of the arm 120. The chisel 140 has a shape having a convex curved surface and a flat surface opposite thereto, the curved surface facing the inner wall of the container 110, and is provided so that the distance between the curved surface and the container 110 is a predetermined length. Thus, the chisel 140 can rotate along the inner wall of the container 110 while maintaining a predetermined distance from the inner wall as the arm 120 rotates.
[0089] In addition, a scraper 150 is provided at the other end of the arm 120. The scraper 150 is a plate-shaped member, and is provided such that the distance between the scraper 150 and the container 110 is a predetermined length, similarly to the chisel 140. Thus, the scraper 150 can scrape the vicinity of the inner wall of the container 110 as the arm 120 rotates.
[0090] Note that the rotating shaft 130 is connected to a rotation drive device (not shown) provided outside the container 110 , thereby being able to rotate the arm 120 .
[0091] In addition, the container 110 can be kept sealed during the driving process of the powder coating device 101, and the inside can be kept in a reduced pressure (vacuum) state or a state replaced with various gases. It should be noted that the container 110 is preferably replaced with an inert gas such as nitrogen or argon.
[0092] Next, a method for producing the insulator-coated soft magnetic particles 1 using the powder coating apparatus 101 will be described.
[0093] First, the core particles 2 and the insulating particles 3 are placed in the container 110. Next, the container 110 is closed and the arm 120 is rotated.
[0094] Here, Figure 3 The state of the powder coating device 101 when the chisel 140 is located at the top and the scraper 150 is located at the bottom is shown. Figure 4 The state of the powder coating device 101 is shown when the chisel 140 is located at the bottom and the scraper 150 is located at the top.
[0095] Using scraper 150 as Figure 3 The core particles 2 and the insulating particles 3 are scooped up as shown. Thus, the core particles 2 and the insulating particles 3 are lifted upward along with the rotation of the arm 120, and then fall down to be stirred.
[0096] On the other hand, Figure 4 As shown, when the chisel 140 descends, the core particles 2 and the insulating particles 3 enter the gap between the chisel 140 and the container 110, and they are subjected to compression and friction from the chisel 140 together with the rotation of the arm 120.
[0097] By repeating the above stirring and compression friction actions at high speed, the insulating particles 3 adhere to the surface of the core particles 2 .
[0098] The rotation speed of the arm 120 slightly varies depending on the amount of powder put into the container 110, but is preferably about 300 to 1200 revolutions per minute.
[0099] The pressing force of the chisel 140 when compressing the powder varies depending on the size of the chisel 140 , but is preferably about 30N to 500N, for example.
[0100] In addition, the above-mentioned adhesion of the insulating particles 3 is different from the coating method using an aqueous solution, and can be carried out in a dry state or in an inert gas atmosphere. Therefore, the possibility of moisture or the like being interposed between the core particles 2 and the insulating layer 3 during the process is eliminated, and the long-term durability of the insulating material-coated soft magnetic particles 1 can be improved.
[0101] It should be noted that the insulating particles 3 may also be subjected to surface treatment as required. As a surface treatment, for example, hydrophobic treatment is listed. By implementing the hydrophobic treatment, it is possible to suppress the adsorption of water on the insulating particles 3. Therefore, it is possible to suppress the degradation of the core particles 2 caused by water. In addition, it also has the effect of suppressing the aggregation of the insulating material-coated soft magnetic particles 1.
[0102] Examples of hydrophobic treatment include trimethyl silylation, arylation (eg, phenylation), etc. For trimethyl silylation, for example, a trimethyl silylation agent such as trimethylchlorosilane is used. For arylation, for example, an arylation agent such as halogenated aryl is used.
[0103] The insulator-coated soft magnetic particles 1 obtained as described above satisfy the relationship that the average particle size after heat treatment at 1000° C. is 90% to 110% of the average particle size before heat treatment.
[0104] As described above, such insulator-coated soft magnetic particles 1 have the same average particle size after heat treatment as before heat treatment, and therefore, for example, show good filling properties even after powder compacting. That is, since the core particles 2 have a base 2a and an oxide film 2b, it is not easy for the particles to interact with each other, such as sintering. Therefore, even after powder compacting, the insulator-coated soft magnetic particles 1 can be densely filled into every corner of the forming mold. Thus, a powder compact with high forming density and good magnetic properties such as magnetic permeability and magnetic flux density can be obtained.
[0105] Furthermore, since heat treatment at high temperature can be performed, strain remaining in the insulator-coated soft magnetic particles 1 can be removed more reliably in a shorter time. Thus, a green compact having excellent magnetic properties such as magnetic permeability and coercive force can be efficiently produced.
[0106] Furthermore, by performing a heat treatment at a high temperature before powder compacting, the insulator-coated soft magnetic particles 1 can be obtained, which have the following advantages: even when they are subsequently compacted, strain is unlikely to occur, or even if strain occurs, it can be easily removed by a simple heat treatment.
[0107] It should be noted that the heat treatment at 1000° C. refers to a treatment in which the insulator-coated soft magnetic particles 1 are heated at 1000° C. for 4 hours. The treatment atmosphere is a hydrogen atmosphere.
[0108] In addition, it is preferred that the average particle size of the insulating material coated soft magnetic particles 1 after heat treatment at 1000°C, that is, the average particle size after heat treatment, satisfies the relationship of 92% to 108% of the average particle size before the heat treatment, that is, the average particle size before heat treatment, and more preferably satisfies the relationship of 95% to 105%.
[0109] It should be noted that if the ratio of the average particle size after heat treatment to the average particle size before heat treatment is lower than the aforementioned lower limit, the insulating particles 3 may fall off from the insulator-coated soft magnetic particles 1, and accordingly, the average particle size may be lowered. Therefore, there is a hidden danger of reduced insulation of the insulator-coated soft magnetic particles 1. On the other hand, if the ratio of the average particle size after heat treatment to the average particle size before heat treatment is higher than the aforementioned upper limit, the insulator-coated soft magnetic particles 1 may sinter to each other, and accordingly, the average particle size may be increased. Therefore, in the case where the insulator-coated soft magnetic particles 1 undergo powder pressing and the like, there is a hidden danger of reduced filling properties. In such a case, there is a hidden danger of reduced molding density, and reduced magnetic properties such as magnetic permeability and magnetic flux density of the powder pressed body.
[0110] Note that the average particle size of the insulator-coated soft magnetic particles 1 is a particle size at which 50% of the particle size is accumulated from the smaller diameter side in a mass-based cumulative distribution measured by a laser diffraction particle size distribution measuring apparatus.
[0111] In addition, the relationship related to such an average particle size can be appropriately adjusted according to the particle size and amount of the core particles 2, the particle size and amount of the insulating particles 3, etc. For example, when the amount of the insulating particles 3 is increased, the average particle size after the heat treatment has a tendency to hardly change relative to that before the heat treatment. In addition, when the amount of the core particles 2 is increased, the average particle size after the heat treatment has a tendency to easily change relative to that before the heat treatment.
[0112] In addition, for example, the average particle size of the insulator-coated soft magnetic particles 1 is preferably 1 μm to 50 μm, more preferably 2 μm to 30 μm, and further preferably 3 μm to 15 μm. If the average particle size of the insulator-coated soft magnetic particles 1 is within the aforementioned range, the insulator-coated soft magnetic particles 1 can be used to manufacture a powder magnetic core having low eddy current loss and excellent magnetic properties such as magnetic permeability and magnetic flux density.
[0113] The insulating material-coated soft magnetic particles 1 thus obtained may be classified as necessary. Examples of the classification method include dry classification such as sieve classification, inertial classification, and centrifugal classification, and wet classification such as sedimentation classification.
[0114] In addition, the core particles 2 and the insulating particles 3 may be stirred (mixed) by a stirrer or a mixer before being introduced into the powder coating apparatus 101 .
[0115] In addition, the volume resistivity (specific resistivity) of the powder as a collection of insulator-coated soft magnetic particles 1 when filled in a container is preferably 1 [MΩ·cm] or more, more preferably 5 [MΩ·cm] or more and 1000 [GΩ·cm] or less, and further preferably 10 [MΩ·cm] or more and 500 [GΩ·cm] or less. Such a volume resistivity is achieved without using additional insulating materials, and is therefore based on the insulation itself between the insulator-coated soft magnetic particles 1. Therefore, if an insulator-coated soft magnetic particle 1 that achieves such a volume resistivity is used, the insulator-coated soft magnetic particles 1 are sufficiently insulated from each other, and therefore, the amount of additional insulating material used can be reduced, and accordingly, the ratio of the insulator-coated soft magnetic particles 1 in the powdered magnetic core can be maximized. As a result, a powdered magnetic core that highly combines high magnetic properties and low losses can be achieved. In addition, the insulation breakdown voltage of the powdered magnetic core can be increased.
[0116] It should be noted that the above-mentioned volume resistivity is a value measured as follows.
[0117] First, 1 g of the insulator-coated soft magnetic powder to be measured is filled into an alumina cylinder, and then electrodes made of brass are placed above and below the cylinder.
[0118] Next, while applying a load of 20 kgf between the upper and lower electrodes using a digital force gauge, the resistance between the upper and lower electrodes was measured using a digital multimeter.
[0119] Then, the measured resistance, the distance between electrodes when pressurized, and the cross-sectional area of the inside of the cylinder were substituted into the following calculation formula to calculate the volume resistivity.
[0120] Volume resistivity [MΩ·cm] = resistance [MΩ] × cross-sectional area of the cylinder [cm 2 ] / distance between electrodes [cm]
[0121] It should be noted that when the inner diameter of the cylinder is set to 2r [cm], it can be 2 [cm 2 ] Calculate the cross-sectional area of the cylinder. In this measurement, the inner diameter of the cylinder is set to 0.8 [cm].
[0122] In addition, the distance between electrodes during pressurization was set to 0.425 [cm].
[0123] In addition, particles having insulating properties other than the insulating particles 3 may be used together with the insulating particles 3 .
[0124] As particles having insulating properties other than the insulating particles 3, for example, glass particles are mentioned.
[0125] As components contained in the glass particles, for example, Bi2O3, B2O3, SiO2, Al2O3, ZnO, SnO, P2O5, PbO, Li2O, Na2O, K2O, MgO, CaO, SrO, BaO, Gd2O3, Y2O3, La2O3, Yb2O3, etc. are listed, and one or more of them are used.
[0126] In addition, non-conductive inorganic materials such as silicon materials may also be used.
[0127] It should be noted that the amount of the insulating particles other than the insulating particles 3 added is preferably 50% by mass or less of the insulating particles 3 , and more preferably 30% by mass or less.
[0128] The insulating material coated soft magnetic particles 1 obtained as described above are subjected to heat treatment. By performing the heat treatment, as described above, the strain remaining in the insulating material coated soft magnetic particles 1 can be removed (annealing). This can realize a powder magnetic core having excellent magnetic properties such as coercive force.
[0129] The temperature of the heat treatment is appropriately set according to the type of soft magnetic material, but is preferably 600°C to 1200°C, and more preferably 800°C to 1100°C. By setting the temperature of the heat treatment within the above range, the strain remaining in the insulating material-coated soft magnetic particles 1 can be more reliably removed in a shorter time. Thus, a powder compact with good magnetic properties can be efficiently manufactured.
[0130] Furthermore, by performing heat treatment at such a temperature before powder compacting, the insulator-coated soft magnetic particles 1 can be obtained, which have the following advantages: even when they are subsequently compacted, strain is unlikely to occur, or even if strain occurs, it can be easily removed by simple heat treatment.
[0131] On the other hand, the heat treatment time is appropriately set according to the heat treatment temperature, but is preferably 30 minutes to 10 hours, more preferably 1 hour to 6 hours. By setting the heat treatment time within the above range, the strain remaining in the insulator-coated soft magnetic particles 1 can be fully removed.
[0132] In addition, the atmosphere of heat treatment is not particularly limited, and there are oxidizing atmospheres including oxygen, air, etc., reducing atmospheres including hydrogen, ammonia decomposition gas, etc., inactive atmospheres including nitrogen, argon, etc., reduced pressure atmospheres in which any gas is decompressed, etc., but reducing atmospheres, inactive atmospheres or reduced pressure atmospheres are preferred, and reducing atmospheres are more preferred. Thus, it is possible to suppress the film thickness increase of the oxide film 2b of the core particle 2 while annealing. As a result, it is possible to obtain an insulator-coated soft magnetic particle 1 having good magnetic properties and a high adhesion strength of the insulating particle 3.
[0133] [Powder cores and magnetic components]
[0134] Next, the powder magnetic core according to the present embodiment and the magnetic element according to the present embodiment will be described.
[0135] The magnetic element involved in this embodiment can be applied to various magnetic elements with magnetic cores, such as choke coils, inductors, noise filters, reactors, transformers, motors, actuators, antennas, electromagnetic wave absorbers, solenoid valves, and generators. In addition, the powder core involved in this embodiment can be applied to the magnetic cores of these magnetic elements.
[0136] Hereinafter, two types of choke coils will be described as examples of magnetic components.
[0137] <First Embodiment>
[0138] First, a choke coil to which the magnetic element according to the first embodiment is applied will be described.
[0139] Figure 5 It is a schematic diagram (plan view) showing a choke coil to which the magnetic element according to the first embodiment is applied.
[0140] Figure 5 The choke coil 10 shown has a ring-shaped (ring-shaped) powder magnetic core 11 and a conductive wire 12 wound around the powder magnetic core 11. Such a choke coil 10 is generally called a ring coil.
[0141] The powdered magnetic core 11 is obtained by mixing the insulator-coated soft magnetic powder including the aforementioned insulator-coated soft magnetic particles 1, a binder (adhesive) and an organic solvent, supplying the obtained mixture to a molding die, and performing pressurization and molding. That is, the powdered magnetic core 11 includes the insulator-coated soft magnetic powder involved in this embodiment. Such a powdered magnetic core 11 has good insulation and heat resistance between particles, so the eddy current loss is small even at high temperatures. In addition, since the coercive force of the insulator-coated soft magnetic powder can be reduced by heat treatment at high temperatures, the hysteresis loss is reduced. As a result, the low loss (improvement of magnetic properties) of the powdered magnetic core 11 is achieved. When the powdered magnetic core 11 is mounted on electronic equipment, etc., the power consumption of the electronic equipment, etc. can be reduced, or high performance can be achieved, which helps to improve the reliability of the electronic equipment, etc. at high temperatures.
[0142] In addition, as described above, the choke coil 10 as an example of a magnetic element includes a powder core 11. As a result, the choke coil 10 achieves high performance and low iron loss. As a result, when the choke coil 10 is installed in an electronic device, the power consumption of the electronic device can be reduced or high performance can be achieved, which can help improve the reliability of the electronic device at high temperatures.
[0143] As the constituent material of the binder for manufacturing the powder magnetic core 11, for example, organic materials such as silicone resin, epoxy resin, phenolic resin, polyamide resin, polyimide resin, polyphenylene sulfide resin, etc.; phosphates such as magnesium phosphate, calcium phosphate, zinc phosphate, manganese phosphate, cadmium phosphate, silicates such as sodium silicate (water glass), etc. can be listed, and thermosetting polyimide or epoxy resin is particularly preferred. These resin materials are easily cured by heating and have excellent heat resistance. Therefore, the manufacturing ease and heat resistance of the powder magnetic core 11 can be improved.
[0144] It should be noted that the binder may be used as needed or may be omitted. Even in such a case, insulation between particles can be achieved in the insulator-coated soft magnetic powder, thereby suppressing loss caused by conduction between particles.
[0145] In addition, the ratio of the binder to the insulator-coated soft magnetic powder slightly varies depending on the target saturation magnetic flux density, mechanical properties, allowable eddy current loss, etc. of the powder magnetic core 11 to be manufactured, and is preferably between 0.5 mass% and 5.0 mass%, and more preferably between 1.0 mass% and 3.0 mass%. Thus, the powder magnetic core 11 having excellent magnetic properties such as saturation magnetic flux density and magnetic permeability can be obtained while the particles of the insulator-coated soft magnetic powder are fully bonded to each other.
[0146] The organic solvent is not particularly limited as long as it can dissolve the binder, and examples thereof include various solvents such as toluene, isopropyl alcohol, acetone, methyl ethyl ketone, chloroform, and ethyl acetate.
[0147] It should be noted that various additives may be added to the mixture for any purpose as needed.
[0148] On the other hand, as a constituent material of the conductive wire 12, a material having high conductivity can be cited, for example, a metal material including Cu, Al, Ag, Au, Ni, and the like.
[0149] It should be noted that it is preferable to provide an insulating surface layer on the surface of the conductive wire 12. This can reliably prevent a short circuit between the powder core 11 and the conductive wire 12. Examples of the constituent material of such a surface layer include various resin materials.
[0150] Next, a method for manufacturing the choke coil 10 will be described.
[0151] First, the insulator-coated soft magnetic powder, a binder, various additives, and an organic solvent are mixed to obtain a mixture.
[0152] Next, the mixture is dried to obtain a block-shaped dry product, and the dry product is pulverized to obtain a granulated powder.
[0153] Next, the granulated powder is molded into the shape of a powder magnetic core to be produced to obtain a molded body.
[0154] The molding method in this case is not particularly limited, and examples thereof include press molding, extrusion molding, injection molding, and the like. It should be noted that the shape and size of the molded body are determined by estimating the amount of shrinkage when the molded body is subsequently heated. In addition, the molding pressure during press molding is set to 1 t / cm 2 (98MPa) above 10t / cm 2 (981MPa) or less.
[0155] Next, the obtained molded body is heated to solidify the binder, thereby obtaining the powder magnetic core 11. At this time, the heating temperature slightly varies depending on the composition of the binder, but when the binder is composed of an organic material, it is preferably set to about 100° C. to about 500° C., and more preferably to about 120° C. to about 250° C. In addition, the heating time varies depending on the heating temperature, and is set to about 0.5 hours to about 5.0 hours.
[0156] As described above, the powder core 11 obtained by pressurizing and molding the insulator-coated soft magnetic powder according to the present embodiment and the choke coil 10 obtained by winding the conductive wire 12 along the outer peripheral surface of the powder core 11 can be obtained.
[0157] It should be noted that the shape of the powder core 11 is not limited to Figure 5 The ring shape shown may be, for example, a shape in which a part of the ring is cut out, or may be a rod shape.
[0158] In addition, the powder core 11 may include soft magnetic powders other than the insulator-coated soft magnetic powders according to the above-mentioned embodiment as required. In this case, the mixing ratio of the insulator-coated soft magnetic powders according to the embodiment and other soft magnetic powders is not particularly limited but can be set arbitrarily. In addition, two or more other soft magnetic powders may be used.
[0159] <Second embodiment>
[0160] Next, a choke coil to which the magnetic element according to the second embodiment is applied will be described.
[0161] Figure 6 It is a schematic diagram (perspective perspective view) showing a choke coil to which the magnetic element according to the second embodiment is applied.
[0162] Hereinafter, a choke coil to which the second embodiment is applied will be described. In the following description, the differences from the choke coil to which the first embodiment is applied will be described, and descriptions of the same matters will be omitted.
[0163] Figure 6 The choke coil 20 shown is formed by burying the conductive wire 22 formed into a coil shape inside the powder magnetic core 21. That is, the choke coil 20 is formed by molding the conductive wire 22 with the powder magnetic core 21.
[0164] The choke coil 20 of this type can be easily formed into a relatively small size. Furthermore, when manufacturing such a small choke coil 20, by using a powder core 21 with a large saturation magnetic flux density and magnetic permeability and a small loss, a low-loss, low-heat choke coil 20 that can handle a large current can be obtained even in a small size.
[0165] Furthermore, since the lead wire 22 is buried inside the powder core 21, a gap is unlikely to be generated between the lead wire 22 and the powder core 21. Therefore, vibration caused by magnetostriction of the powder core 21 can be suppressed, and noise associated with the vibration can also be suppressed.
[0166] When manufacturing the choke coil 20 as described above, first, the conductive wire 22 is placed in the cavity of the molding die, and the cavity is filled with granulated powder containing the insulating material coated soft magnetic powder. That is, the granulated powder is filled so as to contain the conductive wire 22 .
[0167] Next, the granulated powder is pressurized together with the conductive wire 22 to obtain a compact.
[0168] Next, the molded body is subjected to heat treatment in the same manner as in the first embodiment, thereby solidifying the binder and obtaining the powder core 21 and the choke coil 20 .
[0169] It should be noted that the powder core 21 may also contain soft magnetic powders other than the insulator-coated soft magnetic powders of the above-mentioned embodiment as required. In this case, the mixing ratio of the insulator-coated soft magnetic powders of the embodiment and other soft magnetic powders is not particularly limited and can be set arbitrarily. In addition, two or more other soft magnetic powders may be used.
[0170] [Electronic equipment]
[0171] Next, based on Figure 7 to Figure 9 An electronic device including the magnetic element according to the present embodiment (electronic device according to the present embodiment) will be described in detail.
[0172] Figure 7 1 is a perspective view showing the structure of a mobile (or notebook) personal computer to which an electronic device having a magnetic element according to an embodiment is applied. In the figure, a personal computer 1100 is composed of a main body 1104 having a keyboard 1102 and a display unit 1106 having a display unit 100, and the display unit 1106 is rotatably supported on the main body 1104 via a hinge structure. Such a personal computer 1100 has a built-in magnetic element 1000 such as a choke coil, an inductor, a motor, etc. for a switching power supply.
[0173] Figure 8 1 is a plan view showing the structure of a smart phone to which an electronic device having a magnetic element according to an embodiment is applied. In the figure, a smart phone 1200 includes a plurality of operation buttons 1202, an earpiece 1204, and a microphone 1206, and a display unit 100 is arranged between the operation buttons 1202 and the earpiece 1204. Such a smart phone 1200 has a magnetic element 1000 such as an inductor, a noise filter, and a motor built in.
[0174] Fig. 913 is a perspective view showing the structure of a digital camera to which an electronic device having a magnetic element according to an embodiment of the present invention is applied. It should be noted that the connection with an external device is also briefly shown in the figure. The digital camera 1300 uses an imaging element such as a CCD (Charge Coupled Device) to perform photoelectric conversion on an optical image of a subject and generates an imaging signal (image signal).
[0175] A display unit 100 is provided on the back of a housing (main body) 1302 of the digital camera 1300. The display unit 100 is configured to display a captured image based on an image pickup signal of the CCD, and the display unit 100 functions as a viewfinder that displays the subject as an electronic image. In addition, a light receiving unit 1304 including an optical lens (image pickup optical system), a CCD, etc. is provided on the front side (back side in the figure) of the housing 1302.
[0176] When the photographer confirms the subject image displayed on the display unit 100 and presses the shutter button 1306, the imaging signal of the CCD at that time is transmitted and stored in the memory 1308. In addition, in the digital camera 1300, a video signal output terminal 1312 and an input / output terminal 1314 for data communication are provided on the side of the housing 1302. And, as shown in the figure, a television monitor 1430 is connected to the video signal output terminal 1312, and a personal computer 1440 is connected to the input / output terminal 1314 for data communication, respectively, as needed. Furthermore, the imaging signal stored in the memory 1308 is configured to be output to the television monitor 1430 and the personal computer 1440 by a predetermined operation. In such a digital camera 1300, for example, a magnetic element 1000 such as an inductor and a noise filter is also built in.
[0177] Such an electronic device includes the aforementioned magnetic element and therefore has excellent reliability even at high temperatures.
[0178] It should be noted that the electronic device involved in this embodiment can be applied to Figure 7 Personal computers (mobile personal computers), Figure 8 Smartphones, Fig. 9In addition to digital cameras, the present invention can also be applied to, for example, portable phones, tablet terminals, wearable terminals, watches, inkjet ejection devices (such as inkjet printers), laptop personal computers, televisions, cameras, video recorders, car navigation devices, pagers, electronic notepads (including those with communication functions), electronic dictionaries, calculators, electronic game equipment, word processors, workstations, videophones, anti-theft TV monitors, electronic binoculars, POS terminals, medical equipment (such as electronic thermometers, blood pressure monitors, blood glucose meters, electrocardiogram measuring devices, ultrasonic diagnostic devices, electronic endoscopes), fish finders, various measuring equipment, measuring instruments (such as measuring instruments for vehicles, aircraft, and ships), mobile body control equipment (such as automobile drive control equipment, etc.), flight simulators, etc.
[0179] [Mobile body]
[0180] Next, based on Fig.10 A moving object including the magnetic element according to the present embodiment (moving object according to the present embodiment) will be described.
[0181] Fig.10 This is a perspective view showing a vehicle to which a moving object including a magnetic element according to the embodiment is applied.
[0182] The magnetic element 1000 is built into the automobile 1500. Specifically, the magnetic element 1000 is built into various automobile parts such as a car navigation system, an anti-lock braking system (ABS), an engine control unit, a battery control unit of a hybrid car or an electric car, a body posture control system, an electronic control unit such as an automatic driving system, a drive motor, a generator, an air conditioning unit, and a battery.
[0183] Such a moving body includes the aforementioned magnetic element and therefore has excellent reliability even at high temperatures.
[0184] It should be noted that the mobile body involved in this embodiment can be applied to Fig.10 In addition to the automobile shown, the present invention can be applied to, for example, a two-wheeled vehicle, a bicycle, an aircraft, a helicopter, an unmanned aerial vehicle, a ship, a submarine, a railway vehicle, a rocket, a spacecraft, and the like.
[0185] As mentioned above, although this invention was demonstrated based on the preferred embodiment, this invention is not limited to this, and the structure of each part can be replaced with arbitrary structures which have the same function.
[0186] Furthermore, in the present invention, arbitrary structures may be added to the above-mentioned embodiments.
[0187] In the above-mentioned embodiment, a powder core is cited as an example of application of the insulator-coated soft magnetic powder of the present invention, but the application example is not limited to this. For example, it may be a magnetic device including a powder core, such as a magnetic shielding plate and a magnetic head.
[0188] Furthermore, the shapes of the powder magnetic core and the magnetic element are not limited to the shapes shown in the drawings, and may be any shapes.
[0189] [Example]
[0190] Next, specific embodiments of the present invention will be described.
[0191] 1. Manufacturing of soft magnetic powder coated with insulation
[0192] (Example 1)
[0193] First, a metal powder (core particles) of a Fe-Si-Cr alloy produced by a water atomization method was prepared. Note that the average particle size of the metal powder was 10 μm.
[0194] On the other hand, alumina ceramic powder (insulating particles) was prepared. The average particle size of the powder was 18 nm.
[0195] Next, the metal powder and the ceramic powder are put into a friction mixer to generate a mechanical compression friction action, thereby causing the ceramic powder to adhere to the surface of the metal particles.
[0196] Next, the metal powder to which the ceramic powder adhered was subjected to heat treatment, thereby obtaining an insulator-coated soft magnetic powder. It should be noted that the heat treatment was performed by heating at a temperature of 1000° C. for 4 hours at a heating rate of 5° C. / min in a hydrogen atmosphere.
[0197] (Example 2 to Example 13)
[0198] Except that the production conditions were changed as shown in Table 1 or Table 2, the insulator-coated soft magnetic powder was obtained in the same manner as in Example 1.
[0199] It should be noted that trimethylsilylating agent was used in the hydrophobic treatment of Example 2 and Example 5.
[0200] On the other hand, in the hydrophobic treatment of Example 7, an arylating agent (phenylating agent) was used.
[0201] In Example 8, a mixture of aluminum oxide powder and silicon oxide powder was used as the ceramic powder. Note that the mixing ratio was set to a volume ratio of 1:1.
[0202] (Example 14 to Example 16)
[0203] As the metal powder, Fe—Cr—Al alloy metal powder produced by a water atomization method was used, and except that the production conditions were changed as shown in Table 2, the same procedure as in Example 1 was carried out to obtain insulator-coated soft magnetic powders.
[0204] (Comparative Example 1, Comparative Example 2)
[0205] Insulator-coated soft magnetic powders were obtained in the same manner as in Example 1 except that the metal powder of the Fe—Si—Cr alloy produced by the gas atomization method was used.
[0206] It should be noted that the presence or absence of an oxide film was checked for the metal powder used, and no oxide film was found.
[0207] (Comparative Example 3, Comparative Example 4)
[0208] Insulator-coated soft magnetic powders were obtained in the same manner as in Example 1 except that glass powders composed of the glass components shown in Table 1 were used instead of the ceramic powders.
[0209] It should be noted that the obtained insulator-coated soft magnetic powder was subjected to heat treatment, which resulted in aggregation and made it impossible to measure the average particle size.
[0210] (Comparative Example 5)
[0211] Except that the production conditions were changed as shown in Table 2, the same procedure as in Example 1 was carried out to obtain an insulator-coated soft magnetic powder.
[0212] (Reference example)
[0213] An insulator-coated soft magnetic powder was obtained in the same manner as in Example 1 except that the formation of the insulating layer was omitted.
[0214] It should be noted that the obtained insulator-coated soft magnetic powder was subjected to heat treatment, which resulted in aggregation and made it impossible to measure the average particle size.
[0215] 2. Evaluation of soft magnetic powder coated with insulation
[0216] 2.1 Determination of the average particle size of the insulating material-coated soft magnetic powder before and after heat treatment
[0217] The average particle diameters of the insulator-coated soft magnetic powders obtained in the examples, comparative examples and reference examples before and after the heat treatment were measured.
[0218] Next, the ratio of the average particle size after the heat treatment to the average particle size before the heat treatment was calculated.
[0219] Tables 1 and 2 show the calculation results.
[0220] 2.2 Determination of coercivity of soft magnetic powder coated with insulating material
[0221] The coercive force of each of the insulator-coated soft magnetic powders obtained in the examples, comparative examples, and reference examples was measured under the following measurement conditions.
[0222] <Measurement conditions of coercive force>
[0223] ·Measurement device: Magnetization measurement device (VSM system manufactured by Tamagawa Manufacturing Co., Ltd., TM-VSM1230-MHHL)
[0224] Then, the measured coercive force was evaluated according to the following evaluation criteria.
[0225] <Evaluation criteria of coercive force>
[0226] A: Coercivity less than 3.0 [Oe]
[0227] B: Coercive force is 3.0 [Oe] or more and less than 3.5 [Oe]
[0228] C: Coercive force is 3.5 [Oe] or more and less than 5.0 [Oe]
[0229] D: Coercive force is 5.0 [Oe] or more and less than 7.0 [Oe]
[0230] E: Coercive force is 7.0 [Oe] or more and less than 10.0 [Oe]
[0231] F: Coercive force is 10.0 [Oe] or more
[0232] Tables 1 and 2 show the measurement results.
[0233] 2.3 Determination of dielectric breakdown voltage of soft magnetic powder coated with insulating material
[0234] 2 g of the insulator-coated soft magnetic powder obtained in each of the Examples, Comparative Examples and Reference Examples was filled into an alumina cylindrical container having an inner diameter of 8 mm, and brass electrodes were placed above and below the container.
[0235] Next, a digital force gauge was used to apply 40kg / cm2 of force between the upper and lower electrodes. 2 pressure.
[0236] Next, while the load was maintained, a voltage of 50 V was applied between the upper and lower electrodes for two seconds at room temperature (25° C.), and the resistance between the electrodes was measured using a digital multimeter.
[0237] Next, the voltage was increased to 100 V and then applied for 2 seconds, and the resistance between the electrodes was measured again.
[0238] After that, the resistance between the electrodes was repeatedly measured while the voltage was increased by 50 V at a time, such as 200 V, 250 V, 300 V, ... Thus, the voltage increase and measurement were repeated until insulation breakdown occurred.
[0239] Note that, when insulation breakdown did not occur even when the voltage was increased to 1000 V, the measurement was terminated at that point.
[0240] The above measurements were performed three times each while changing the powder to new powder. Tables 1 and 2 show the minimum measured values.
[0241] 2.4 Determination of filling properties of soft magnetic powder coated with insulation
[0242] The apparent density of the insulator-coated soft magnetic powder obtained in each of the Examples, Comparative Examples, and Reference Examples was measured.
[0243] It should be noted that the apparent density of the insulator-coated soft magnetic powder is measured according to the apparent density measurement method for metal powder specified in JIS Z 2504:2012, and the unit is g / cm 3 .
[0244] Next, the ratio of the apparent density of the insulator-coated soft magnetic powder to the true density was calculated and evaluated according to the following evaluation criteria. Note that the unit of true density is g / cm 3 .
[0245] <Evaluation criteria for filling performance>
[0246] A: 0.40 or more
[0247] B: 0.35 or more and less than 0.40
[0248] C: 0.30 or more and less than 0.35
[0249] D: less than 0.30
[0250] E: Unable to measure due to sintering
[0251] Tables 1 and 2 show the evaluation results.
[0252] [Table 1]
[0253]
[0254] [Table 2]
[0255]
[0256] It is clear from Tables 1 and 2 that the insulator-coated soft magnetic powders of each embodiment have better coercive force and dielectric breakdown voltage of the powder compact than the insulator-coated soft magnetic powders of each comparative example and reference example. In addition, it can be confirmed that the ratio of apparent density to true density of the insulator-coated soft magnetic powders of each embodiment is high, and the filling property is good.
Claims
1. An insulator-coated soft magnetic powder, characterized in that: With core particles and insulating particles, The core particle comprises a base and an oxide film, The base includes a soft magnetic material, the oxide film is provided on a surface of the base and includes an oxide of an element contained in the soft magnetic material, The insulating particles are mechanically adhered to the surface of the core particles and have insulating properties. The oxide film contains a glass-forming component and a glass-stabilizing component or a chemically stable chromium oxide. The insulating material contained in the insulating particles has a Mohs hardness of 6 or more, The insulator-coated soft magnetic powder has an average particle size after heat treatment at 1000° C. that is 90% to 110% of the average particle size before heat treatment.
2. The insulator-coated soft magnetic powder according to claim 1, characterized in that: The insulating particles are in a state of being sunken into the oxide film or in a state of components of the insulating particles and the oxide film being mutually diffused.
3. The insulator-coated soft magnetic powder according to claim 1, characterized in that: The oxide film has a thickness of 5 nm to 200 nm.
4. The insulator-coated soft magnetic powder according to claim 1, characterized in that: In the case where the insulating particles include an oxide, The glass-forming component and the oxide contained in the insulating particles are vitrified.
5. The insulator-coated soft magnetic powder according to claim 1, characterized in that: The insulating particles include at least one of aluminum oxide, silicon oxide, zirconium oxide and silicon nitride.
6. The insulator-coated soft magnetic powder according to claim 1, characterized in that: The core particles have an average particle size of 1 μm or more and 50 μm or less.
7. The insulator-coated soft magnetic powder according to any one of claims 1 to 6, characterized in that: The insulating particles are subjected to a hydrophobic treatment.
8. A powder magnetic core, characterized in that: The invention comprises the insulator-coated soft magnetic powder according to any one of claims 1 to 7.
9. A magnetic element, characterized in that: A powder magnetic core according to claim 8 is provided.
10. An electronic device, characterized in that: A magnetic element according to claim 9.
11. A mobile object, characterized in that: A magnetic element according to claim 9.
Citation Information
Patent Citations
Soft magnetic particle powder, manufacturing method thereof, and powder magnetic core containing the powder
JP2009188270A
Surface treatment process for surface alumina ceramic layer of iron-chromium-aluminum alloy
CN102503560A
Soft magnetic material powder and manufacturing method thereof, and magnetic core and manufacturing method thereof
US20170162307A1